Unfurling Fern - Shardlow, Mignon; Elliott, Ron (FERN, 2019)
The Fremantle Environmental Research Network (FERN) is a community kitchen and garden run by volunteers. In September 2019 they were evicted from their long term home on High Street. They can no longer provide the community meals their volunteers have offered twice a week for years. The Fremantle council has offered to relocate them, but they still have nowhere to go.